Process analytical technology for the food industry - Fagan, Colette; Cullen, P.J; O'Donnell, Colm P. (Food Engineering Series, 2014)
The Process Analytical Technology (PAT) initiative aims to move from a paradigm of 'testing quality in' to 'building quality in by design'. It can be defined as the optimal application of process analytical technologies, feedback process control strategies, information management tools, and/or product-process optimization strategies.  Recently, there have been significant advances in process sensors and in model-based monitoring and control methodologies, leading to enormous opportunities for improved performance of food manufacturing processes and for the quality of food products with the adoption of PAT. Improvements in process efficiency, reduced product variability, enhanced traceability, process understanding, and decreased risk of contamination are some of the benefits arising from the introduction of a PAT strategy in the food industry.  Process Analytical Technology for the Food Industry reviews established and emerging PAT tools with potential application within the food processing industry. The book will also serve as a reference for industry, researchers, educators, and students by providing a comprehensive insight into the objectives, challenges, and benefits of adopting a Process Analytical Technology strategy in the food industry. About the Editors Professor Colm O'Donnell is Vice Principal (Teaching & Learning) in the College of Engineering and Architecture at University College Dublin. He leads a research team working on a range of PAT and Novel Processing Technology research projects in the UCD School of Biosystems Engineering. He has published widely in the area of PAT for dairy processing and holds two patents in this area.  Dr. Colette Fagan is a Lecturer in Food Processing Science and Director of the Food Processing Centre at the University of Reading. Her research focuses on PAT, in particular its application to dairy processing. She has published over 40 journal papers and book chapters and holds two patents for novel sensing technologies used in the control of dairy processing.  Dr. PJ Cullen teaches process engineering at the School of Chemical Engineering, University of New South Wales, Sydney, Australia. His current research interests include the development of novel hyperspectral, multipoint spectroscopy and particle imaging systems for process control. He initiated the "Food Quality, Safety & Analysis" sessions at IFPAC, the world's leading PAT conference, and is a member of its organizing committee. He has published over 100 journal papers and book chapters.